The Relationship Between Emotional Intelligence And Work Engagement Among Employees In Small Growing Company - Mochamad Zainun Abadi; Zun Azizul Hakim (Universitas Muhammadiyah Purwokerto, 2025)
Low work engagement in growing companies often leads to high turnover and decreased productivity. This study examines the role of personal resources in maintaining employee performance by investigating the correlation between emotional intelligence (EI) and work engagement. Using a total sampling technique, the research involved 50 male employees at UD Jaya Kapuk, a small growing company. This homogenous and controlled sample was intentionally selected to minimize confounding variables such as gender and generational differences, ensuring high internal validity within the specific organizational context. Data analysis using Pearson's correlation revealed a strong positive correlation (r = 0.652, p < 0.001) between EI and work engagement. This finding suggests that higher EI is significantly associated with higher work engagement, providing a baseline for targeted interventions in similar small-scale enterprises. Future research may extend these findings to broader demographics to complement the specific insights established in this study.